The association between different family environments and adolescent depressive symptoms: the mediating effects of internet addiction and peer relationships - Feng, Haiqing; Jiang, Kefan; Lu, Yufei; Liu, Dingmeng; Zhu, Aihui; Zhou, Guangzhong; Gao, Yuexia; Lu, Qingyun (Frontiers in Psychiatry, 2025)
IntroductionThis study aims to examine the relationship between different family environments and depressive symptoms in adolescents, with a particular focus on the association between the family emotional environment and depressive symptoms, as well as the mediating effects of internet addiction and peer relationships.MethodsUsing cluster sampling, 2,825 adolescents were surveyed using the questionnaire on basic family circumstances, the parenting style scale (PBI), the children’s perception of Interparental conflict scale (CPIC), the Internet addiction diagnosis scale (YDQ), the peer relationship scale, and the child depression scale (CDI).Results(1) The family emotional environment can be divided into low emotional support families (52.4%) and high emotional support families (47.6%), and the family economic environment can be divided into low socioeconomic status (SES) families (71.3%) and high SES families (28.7%);(2) The family emotional environment was linked to depressive symptoms in adolescents (r= - 0.07, P < 0.01), while the family economic environment was not (P>0.05). (3) Internet addiction and peer relationships mediated the relationship between family emotional environment and adolescent depressive symptoms after controlling for gender, home location, and only-child status.DiscussionThe study results emphasize the importance of creating a positive emotional environment at home, which is an effective measure for alleviating symptoms of depression in adolescents, reducing the risk of internet addiction, and improving the quality of peer relationships.